Folic acid supplementation in European women of reproductive age and during pregnancy with excessive weight: a systematic review - Federica Loperfido; Francesca Sottotetti; Irene Bianco; Dana El Masri; Beatrice Maccarini; Chiara Ferrara; Antonio Limitone; Hellas Cena; Rachele De Giuseppe (Reproductive Health)
Abstract Objective Neural tube defects (NTDs), well-known consequences of folate deficiency, are the second most common cause of serious birth defects, affecting approximately one in a thousand pregnancies in Europe. Maternal folate deficiency before conception and during early pregnancy has been suggested as the most important preventable risk factor for NTDs; thus women should be supplemented before conception with 0.4 mg of folic acid (FA) until the first trimester of gestation. Findings have described a positive association between elevated Body Mass Index (BMI) and birth defect risk; data on plasma folate levels in pregnant women with obesity have shown values lower than recommended because of a state of chronic low-grade inflammation, resulting in increased metabolic demands. Nowadays, disparities exist regarding the recommended dose of FA in women at risk, including women of childbearing age with excessive weight. Therefore, this systematic review aimed to investigate if European childbearing age/pregnant women with overweight/obesity are supplemented according to the current country-specific FA recommendations and whether the dosage of 5 mg recommended for pregnant women with obesity is effective in preventing NTDs. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. An electronic database search of manuscripts was carried out in Web of Sciences, PubMed and Medline. The quality of the included studies was assessed by using the Quality Assessment for Diverse Studies statement. Results Out of 1718 records identified, 8 manuscripts met all the inclusion criteria. Overall, the results showed that pregnant women with obesity adherent to FA recommendations ranged between 4% and 9.5%. Furthermore, the majority (61%) started the supplementation after conception, highlighting that European pregnant women are not particularly adherent to recommendations during the period of greatest need. Conclusions The scarce adherence to the current guidelines shows an urgent need to standardize the recommendations across European countries. Particularly, women of childbearing age with excess weight should be monitored assessing serum folate, RBC folate, and homocysteine levels developing tailored supplementation protocols, to counteract the occurrence of NTDs.